Tackling high cost of living in Malaysia: a strategic analysis - Azmi, Nur Adlina; Fitriana, Aulia Regita Dewi; Rohsede, Nur Hidayahtul Aina; Ramden, Nurezzetty Anthasha; Puteh, Fadilah (Faculty of Administrative Science and Policy Studies, 2023)
Inflation, high housing costs, taxes on goods and services, reduced subsidies, low-income levels, expensive education and healthcare, and dependence on imported goods are all challenges that contribute to the high cost of living in Malaysia. In particular, inflation has been a major factor driving up living expenses over time. The Ministry of Domestic Trade and Costs of Living (KPDN) plays a crucial role in addressing this issue. The article used various strategic management techniques like PEST matrix, internal audit matrix, and TOWS matrix to understand the challenges of high cost of living in Malaysia. It also provided valuable recommendations to tackle the problem. The article is helpful in providing insights and solutions to the issue of high cost of living in Malaysia.